Optimizing Company Value: Size, Governance and Financial Performance on the Indonesian Stock Exchange - Ciptha, Andrea; Alamsyahbana, Muhammad Isa; Sarazwati, Raja Yulianita; Indriaty, Novica (Universitas Batanghari Jambi, 2024)
This study aims to investigate how the size of a company and its adherence to good corporate governance affect its value, with a focus on food and beverage companies listed on the IDX during the period from 2020 to 2022. The research sampled 37 companies using purposive sampling. It employed a quantitative approach, with data collected through literature review and web searches, primarily from official agency websites providing relevant reports. Data analysis was conducted using the Econometric Views (E-Views) 12 application. The findings indicate that while company size and good corporate governance do not directly impact financial performance, they do influence company value when financial performance serves as an intermediary variable.